LIFE SKILL EDUCATION AND IT'S IMPLEMENTATION IN STUDY PROGRAMS ISLAMIC RELIGIOUS EDUCATION - Amirudin Amirudin; Iqbal Amar Muzaki (JURNAL TARBIYAH, 2019)
The era of globalization requires humans to have more expertise to work and be competitive. These pressures lead to issues of productivity, efficiency, level of competition, which demand increased performance and quality. In addition to the problem of educated unemployment, it turns out there are still many schools or institutions that have not yet implemented life skills education, so graduates do not have more expertise to develop. Islamic Education Study Program Faculty of Islamic Religion Unsika which is one of the institutions of higher education is obliged to equip students with life skills education, so that graduates are able to compete in the global arena. Life skill education which is most followed by students is the education of reading the Qur'an, practice recitations, practice of worship, basic training of student leadership, and training of preacher and preacher cadres.